Primary and Secondary Kinase Genotypes Correlate With the Biological and Clinical Activity of Sunitinib in Imatinib-Resistant Gastrointestinal Stromal Tumor - Heinrich, Michael C. (American Society of Clinical Oncology, 2008)
PURPOSE: Most gastrointestinal stromal tumors (GISTs) harbor mutant KIT or platelet-derived growth factor receptor α (PDGFRA) kinases, which are imatinib targets. Sunitinib, which targets KIT, PDGFRs, and several other kinases, has demonstrated efficacy in patients with GIST after they experience imatinib failure. We evaluated the impact of primary and secondary kinase genotype on sunitinib activity. PATIENTS AND METHODS: Tumor responses were assessed radiologically in a phase I/II trial of sunitinib in 97 patients with metastatic, imatinib-resistant/intolerant GIST. KIT/PDGFRA mutational status was determined for 78 patients by using tumor specimens obtained before and after prior imatinib therapy. Kinase mutants were biochemically profiled for sunitinib and imatinib sensitivity. RESULTS: Clinical benefit (partial response or stable disease for ≥ 6 months) with sunitinib was observed for the three most common primary GIST genotypes: KIT exon 9 (58%), KIT exon 11 (34%), and wild-type KIT/PDGFRA (56%). Progression-free survival (PFS) was significantly longer for patients with primary KIT exon 9 mutations (P = .0005) or with a wild-type genotype (P = .0356) than for those with KIT exon 11 mutations. The same pattern was observed for overall survival (OS). PFS and OS were longer for patients with secondary KIT exon 13 or 14 mutations (which involve the KIT-adenosine triphosphate binding pocket) than for those with exon 17 or 18 mutations (which involve the KIT activation loop). Biochemical profiling studies confirmed the clinical results. CONCLUSION: The clinical activity of sunitinib after imatinib failure is significantly influenced by both primary and secondary mutations in the predominant pathogenic kinases, which has implications for optimization of the treatment of patients with GIST.